Provision of a Quality, Customer-Focussed and Continually Improving Laboratory Service in Nigeria - Erhabor, O. , Erhabor, T, , Okara, G.C. , Adias, T.C. , Dangana, A. (Sokoto Journal of Medical Laboratory Science)
It is no longer news that a healthier hospital begins with a healthier diagnostic laboratory. The aim of this editorial is to highlight objective steps and evidenced- based best practices that Medical Laboratory Scientist as custodian of laboratory service delivery in Nigeria can implement to ensure the delivery of a quality, customer-focussed and continually improving service to their customers. Provision of a quality, customer-focussed and continually improving diagnostic service is a possibility in Nigeria. However, it can only be achieved by the implementation of evidenced-based best practice. There is need for a paradigm shift in the mind-set of Medical Laboratory Scientist and the implementation of evidenced–based best practices; quality management system oriented service, implementation of quality audits, IQC and EQA, document control, carrying out customer satisfaction surveys and risk analysis, having a robust training and competency testing programme, prompt reporting and objective investigation of all incidents, accidents and near misses, implementing a process-oriented diagnostic service concentrating on the continual identification and removal of waste and all non-value adding activities from the process, implementing the principle of GLP, GMP, infection control, occupational health and housekeeping, pre- acceptance testing (reagent certification) and equipment validation prior to use, implementing governance by having periodic management review meeting and running the service as a business (geared towards meeting the changing requirements of the customer and making profit) and having a long-term strategic planning mind-set.